Leadership and Islamic management: basis for quality education - Lasisi, Abbas Ayodele; Mohd Ali, Hairuddin (IIUM Press, 2011)
A brief study on the relationships between leadership and Islamic management (independent variables) and quality education (dependent variable). The study used quantitative approach namely descriptive statistics and factor analysis. Recommendation for future and in depth research were also presented.